PENGARUH MODAL KERJA TERHADAP PENDAPATAN DENGAN LAMA USAHA SEBAGAI VARIABEL MODERASI (Survei Pada Pedagang Pasar Klithikan Notoharjo Surakarta) - Utami, Setyaningsih Sri; Wibowo, Edi - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT This study aims to analyze (1) the influence of working capital to traders revenue (2) the influence of long of business to traders revenue (3) the effect of working capital to traders revenue with long business as moderating variable. The population in this study are all traders in the Klithikan Notoharjo Market on Surakarta settle as many as 246 people consisting of 9 types of merchandise. Total sample of 70 traders taken by using Stratified Proportional Random Sampling. To test the hypothesis, the researcher uses the moderating regression analysis with standardized residual method. Results of this study indicate that (1) Working capital is positive and significant effect to traders revenue at Klithikan Notoharjo Market on Surakarta, thus supporting hypothesis 1; (2) Long of business is positive and significant effect to traders revenue at Klithikan Notoharjo Market on Surakarta, thus supporting hypothesis 2; (3) Long of business has not moderate the effect of product quality to consumer satisfaction, showed p value (0,088) > 0,05, which means long of business is not a moderating variable or the relationship between the long of business with traders revenue is direct influence. Keywords: working capital, long of business, traders revenue